Financial Statements of Non-Profit Entity Based on ISAK 35 Church of BNKP Resort 1 Gunungsitoli - Sahala Purba; Intan Nazara; Steven Gulo; Vinsensia Ratna; Hellen Sembiring; Boyke Sinurat; Adrian Arya; Jevon Zebua (Institute of Computer Science (IOCS), 2022)
The Church is an Entity whose Purpose is Not to make a Profit. As a result, the Church's financial accountability is of paramount importance. Good Financial Accountability can be presented in accordance with the applicable General Accounting Standards. Financial Accounting Standards No. 35 (ISAK 35) is an Accounting Standard that discusses the Presentation of Financial Reporting for Non-Profit Entities. With the implementation of ISAK 35, users of financial statements can assess the financial performance of the church. This study aims for the Financial Statements of the Banua Niha Keriso Protestant Church (BNKP) in accordance with ISAK 35 where the resulting Financial Statements consist of Financial Statements, Cash Flow Statements and Financial Statements.